Outcomes of Thalassemia Patients Undergoing Hematopoietic Stem Cell Transplantation by Using a Standard Myeloablative versus a Novel Reduced-Toxicity Conditioning Regimen According to a New Risk Stratification - Anurathapan,U. (Elsevier Inc., 2015)
© 2014 American Society for Blood and Marrow Transplantation. Improving outcomes among class 3 thalassemia patients receiving allogeneic hematopoietic stem cell transplantations (HSCT) remains a challenge. Before HSCT, patients who were ≥ 7 years old and had a liver size ≥ 5 cm constitute what the Center for International Blood and Marrow Transplant Research defined as a very high-risk subset of a conventional high-risk class 3 group (here referred to as class 3 HR). We performed HSCT in 98 patients with related and unrelated donor stem cells. Seventy-six of the patients with age < 10 years received the more conventional myeloablative conditioning (MAC) regimen (cyclophosphamide, busulfan, ± fludarabine); the remaining 22 patients with age ≥ 10 years and hepatomegaly (class 3 HR), and in several instances additional comorbidity problems, underwent HSCT with a novel reduced-toxicity conditioning (RTC) regimen (fludarabine and busulfan). We then compared the outcomes between these 2 groups (MAC versus RTC). Event-free survival (86% versus 90%) and overall survival (95% versus 90%) were not significantly different between the respective groups; however, there was a higher incidence of serious treatment-related complications in the MAC group, and although we experienced 6 graft failures in the MAC group (8%), there were none in the RTC group. Based on these results, we suggest that (1) class 3 HR thalassemia patients can safely receive HSCT with our novel RTC regimen and achieve the same excellent outcome as low/standard-risk thalassemia patients who received the standard MAC regimen, and further, (2) that this novel RTC approach should be tested in the low/standard-risk patient population.